FEATURES OF TRANSFORMATION OF THE TRANSPORT AND LOGISTICS SERVICES MARKET IN UKRAINE - Novalska, Nadya; Klymenko, Victoria; Moskalenko, Olena; Selishchev, Sergii (Science-based technologies, 2021)
The article analyzes the features and factors that influenced the process of accelerating the transformation of the transport and logistics services market in Ukraine. According to the results of the analysis of transport and logistics services market in Ukraine since independence, four stages of its formation have been identified. The first stage (early 1990s) was characterized by a low level of logistics services for transport and warehousing processes, ignoring the principles of logistics. In the second stage (second half of the 1990s) the processes of building a distribution system intensified; new partnerships were formed with all market actors; trading companies were developed and the system of warehousing, transportation and promotion of products was updated; powerful international logistics operators were appeared. The third stage (the first decade of the XXI century) was marked by the emergence of the first national logistics companies (2PL- and 3PL-providers), which provided services at the level of international requirements. The fourth stage (the second decade of the XXI century) is characterized by the development of 3PL and 4PL operational activities; transfer of logistics functions to outsourcing by commercial and industrial enterprises; changing the approach to working with clients. The results of the World Bank’s assessment of the level of the logistics system efficiency in Ukraine in terms of individual indicators and their dynamics, as well as the results of expert research of the general state of transport infrastructure development by the European Business Association have been analyzed. Factors that restrict the development of the transport and logistics services market in Ukraine have been determined. Based on the study, the positive trends that are currently observed in the domestic market of transport and logistics services are identified and the components of its development in accordance with modern international requirements are substantiated.